Peran United Nations High Commissioner For Refugee (UNHCR) Dalam Perlindungan Warga Negara Asing (Pengungsi) Di Indonesia (Kajian Warga Negara Asing Di Rumah Detensi Imigrasi Kota Pekanbaru) - Simatupang, Princen; Edorita, Widia; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The development of transportation technology, information and communication encourage the emergence of problems in international law, such as refugees. Displacement and the easier movement of people has also become one of the factors triggering population migration. It became part of the development and dynamics of international law. Strategic Location of Indonesia, causing Indonesia was the destination of refugees. is protected by the Vienna Convention of 1951 on refugees and its 1967 Protocol regulates these refugees. Obligations of the country of origin is no longer able to protect the basic rights of citizens will be taken over by the international community. Efforts are needed to guarantee and ensure that the basic rights of a person to be protected and respected. International Refugee status granted after he declared it worthy of its status as an international refugee by those competent provide such status. In the case of granting such a status we know the two parties, namely the United Nations High Commissioner for Refugee for those who have not yet ratified, and the country for which has been ratified. Kebaradaan immigration detention centers in Indonesia, one of them in the city of Pekanbaru, is in order to run perinta 1951 Convention.Issues that will be examined in this study are: First, How UNHCR Role in Providing Legal Protection for Foreign Nationals (IDPs) in Indonesia (Study foreigners in the detention center Pekanbaru City)? Second, Do Barriers UNHCR in Providing Legal Protection for Foreign Nationals Refugees) in Indonesia (Study WNA In Rudenim Pekanbaru City)? Third, efforts Which Is Taken UNHCR to Address Legal Protection for Foreign Nationals (IDPs) in Indonesia (Study WNA In Rudenim Pekanbaru City)?This type of research is a sociological law research. Source of data used are primary data and secondary data, data collection techniques using interview, and literature study. In this study the authors used a qualitative analysis, in drawing conclusions using inductive method of thinking. Results from this study were first, Role of UNHCR participation in, and implementation of, the Convention and refugee law, Secondly, UNHCR obstacle is lack of co-ordination to the government as well as the difficulty in obtaining information about the valid data Thirdly, UNHCR efforts is to promote the application of refugee law , Suggestions of authors First, UNHCR must increase its human resources in order to support the performance and supervision of UNHCR to Rudenim, Second, UNHCR should memberbaiki existing coordination in the field to the government or the detention center. Third, efforts UNHCR is by approaching and counseling to foreigners.Keywords: Refugees-UNHCR-House Immigration Detention